Vascular Pattern and Density in Clear Cell vs Clear Cell Papillary Renal Cell Carcinoma. (28th October 2020) - Canete-Portillo, S; Rodriguez Pena, M; Wang, D; Netto, G J; Magi-Galluzzi, C; Sanchez, D F
Abstract: Introduction/Objective: Renal cell carcinomas (RCCs) are well-vascularized tumors. Although clear cell RCC (ccRCC) shows a characteristic vascular network, in some cases may show overlapping features with other RCCs. Microvessel density (MVD) and architectural vascular arrangement in RCC have been characterized using CD31 and CD34 immunohistochemical (IHC) stains. To date, no studies have evaluated the vascular distribution in ccRCC compared to clear cell papillary RCC (ccpRCC). We aimed to identify potential differences in MVD, vascular pattern architecture and extent in ccRCC and ccpRCC. Methods: Fifteen cases of ccRCC and 15 cases of ccpRCC were included in the study. ERG IHC stain and Bioquant Osteo 2019 Imaging Analysis Software were used to evaluate MVD in 12 cases (6 ccRCC, 6 ccpRCC). CD34 was used to evaluate architectural vascular pattern and its extent (% of tumor) in all cases. Mann–Whitney U test in STATA version 16.0 was used for statistical analysis. Results: MVD means were 30.64 (CI: 17.9-43.29) in ccRCC and 29.2 (CI: 17.82-40.57) in ccpRCC. CD34 highlighted 4 distinct vascular patterns: lacunae, pseudoacinar, Golgi-like and scattered. The extent of patterns ranged from 0% to 90%. Heterogeneous distribution of different vascular patterns was found in both RCC groups. Although lacunae pattern was present in all RCC cases, pseudoacinar (100.0% vs 31.0%), Golgi-like (53.8% vs 100%) and scattered (53.8% vs 38.0%) patterns showed different distribution in ccRCC vs ccpRCC, respectively. Lacunae+pseudoacinar was the most frequent combination in all ccRCCs; lacunae+Golgi-like was identified in 77% of ccpRCCs. Pseudoacinar was the most extensive pattern in ccRCCs, meanwhile Golgi-like was the predominant pattern in ccpRCCs (p value<0.05). Conclusion: There was no difference in MVD between ccRCC and ccpRCC. However, the extent of vascular patterns pseudoacinar and Golgi-like was significantly different between ccRCC and ccpRCC. Distinct architectural vascular arrangement could help discriminate these entities.